2017
DOI: 10.1039/c7sc01730h
|View full text |Cite
|
Sign up to set email alerts
|

Temporal switching of an amphiphilic self-assembly by a chemical fuel-driven conformational response

Abstract: A unique redox active amphiphilic foldamer that undergoes transient conformation changes that amplify into observable morphology changes in its self-assembly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 66 publications
1
60
0
1
Order By: Relevance
“…Thordarson and Besenius independently utilized redox activity of sulfide and thioether functional groups, respectively to obtain transient self‐assembly. Our group has shown a transient conformational switching in amphiphilic self‐assembly of a charge‐transfer foldamer by coupling the reducing agent to enzymatic oxidation by glucose oxidase. These reports display the importance of redox chemistry to create transient self‐assembly.…”
Section: Methodsmentioning
confidence: 99%
“…Thordarson and Besenius independently utilized redox activity of sulfide and thioether functional groups, respectively to obtain transient self‐assembly. Our group has shown a transient conformational switching in amphiphilic self‐assembly of a charge‐transfer foldamer by coupling the reducing agent to enzymatic oxidation by glucose oxidase. These reports display the importance of redox chemistry to create transient self‐assembly.…”
Section: Methodsmentioning
confidence: 99%
“…[22] This first experimental value of charge carrier mobility in the semiconducting regime complements the previous outstanding conductivity values obtained for TAAin adoped metallic state. [23] In addition, we have shown that the mechanism involved can be used to gain control over the precise placement and orientation of supramolecular polymers in between electrodes,w ith ap recision that cannot yet be achieved by other techniques,u pt ot he bridging of two electrodes of less than 5 mmi nd iameter and over 50 mmi n length by as ingle nanowire.S uch precise control in every aspect of supramolecular polymerization, including localization and orientation at nano-and micrometer scales,is, for the moment, quite unique in the literature.O ther potential implementations resulting from these experiments include for instance:1)spatial control over self-assembly processes in various optoelectronic devices requiring efficient charge transport and ranging from sensors to solar cells, [24,25] 2) use of waste-free electrochemistry tools to control (living) supramolecular polymerization or to create out-of-equilibrium redox environments for self-organized systems, [26] and 3) design of 3D electrical wiring in organogels. To this end, we have used TAAs,b ut one can imagine extending the concept to other molecules with redox functionalities and capable of forming supramolecular polymers or self-assemblies.…”
Section: Angewandte Chemiementioning
confidence: 96%
“…It represents a new tool of fundamental and practical interest for supramolecular chemistry in general. To this end, we have used TAAs, but one can imagine extending the concept to other molecules with redox functionalities and capable of forming supramolecular polymers or self‐assemblies . In addition, we have shown that the mechanism involved can be used to gain control over the precise placement and orientation of supramolecular polymers in between electrodes, with a precision that cannot yet be achieved by other techniques, up to the bridging of two electrodes of less than 5 μm in diameter and over 50 μm in length by a single nanowire.…”
Section: Figurementioning
confidence: 99%